Zones of Strangeness: An Examination of Paranormal and UFO Hot Spots by Peter A. McCue - Clark, Jerome (Journal of Scientific Exploration, 2014)
<!–[if gte mso 9]> <![endif]–> If I may be permitted an autobiographical note, let me to begin by remarking that I read my first UFO book (Edward Ruppelt's Report on Unidentified Flying Objects) in 1957. If I may be permitted an autobiographical note, let me to begin by remarking that I read my first UFO book (Edward Ruppelt's Report on Unidentified Flying Objects) in 1957. Charles Fort soon followed, and uncountable books ensued, culminating in the full-scale immersion from which my multivolume UFO Encyclopedia (1990-1998) eventually emerged. The more one reads works of mainstream scholarship, the more one is struck by the unprofessional quality of so much writing on anomalies. There are, of course, honorable and happy exceptions, if not nearly so many as there ought to be. Many authors don't seem to know how to develop a logical argument with compelling evidence to match (see, for example, my review in JSE 26(3):707-714.) Many book authors give the impression that they have never read a single book of actual history or science. Not a few give every evidence of unfamiliarity with basic English usage, grammar, and punctuation. In the company of such work as this, an intellectually sophisticated consumer is likely to feel more like an anthropologist than a reader. Over the past month, as it happens, I have read (for review) two anomalies books by well-educated, well-informed writers who, while the content of their thinking and reporting was sound enough, sorely needed competent copyeditors to save them from their worst selves. The second of these is Zones of Strangeness by Peter A. McCue, a Scottish psychologist, who is is educated, intelligent, and perceptive. He is also a screamer.